AN ANALOGY OF GENDER-BASED VIOLENCE AND POLICE CORRUPTION IN MATTERS RELATED TO VIOLENCE AGAINST WOMEN DURING THE COVID-19 PANDEMIC - Smart, Caroline (Journal of Anti-Corruption Law, 2023)
In March 2020, an unprecedented new Corona phenomenon began to emerge, governments were forced to impose lockdowns, restrictions, quarantines and isolations globally to contain the virus. While these measures were necessary to stop the spread of this new phenomenon, it exposed the realities of women's gendered lives. In South Africa, the Covid-19 pandemic entwined with two existing endemics: gender-based violence and corruption within the South African Police Service (SAPS). Gender-based violence is a social-ill inextricably linked to gender-based structural inequalities and state institutions riddled with corruption. The exponential rise in gender-based violence related to Covid-19 once again captures the travesty of a police service paralysed by corruption and afflicted by incompetence to execute its tasks. The police service is unable to defend safety and justice when they are perpetrators themselves. The focus of this article is on the surge of gender-based violence as a consequential effect of Covid-19 restrictions, compounded by an unaccountable police service.